2021
DOI: 10.1128/mra.00272-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Thermus thermophilus Strains HB5002 and HB5008, Isolated from Mine Hot Spring in Japan

Abstract: We isolated Thermus thermophilus strains HB5002 and HB5008 from Mine Hot Spring in Japan. Whole-genome sequencing revealed that they showed ∼100% average nucleotide identity to each other, ≥98.53% to the T. thermophilus strains originating from the same spot but ≤97.64% to the T. thermophilus strains from geographically different places in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Automatic annotation was conducted using DFAST v.1.4.0 ( 13 ); the genomic features are summarized in Table 1 . A JSpecies analysis ( 14 ) revealed that the genome sequences of bacterial strains from Arima Hot Spring (four strains presented in this study and two previously documented strains, AA2-20 [ 15 ] and AA2-29 [ 15 ]) showed ANIs of ≥99.21% to each other but of ≤97.86% to six strains originating from Mine Hot Spring (HB8, HB27 [ 4 ], HC11 [ 5 ], HB5002 [ 7 ], HB5008 [ 7 ], and HB5018 [ 6 ]).…”
Section: Announcementmentioning
confidence: 77%
See 1 more Smart Citation
“…Automatic annotation was conducted using DFAST v.1.4.0 ( 13 ); the genomic features are summarized in Table 1 . A JSpecies analysis ( 14 ) revealed that the genome sequences of bacterial strains from Arima Hot Spring (four strains presented in this study and two previously documented strains, AA2-20 [ 15 ] and AA2-29 [ 15 ]) showed ANIs of ≥99.21% to each other but of ≤97.86% to six strains originating from Mine Hot Spring (HB8, HB27 [ 4 ], HC11 [ 5 ], HB5002 [ 7 ], HB5008 [ 7 ], and HB5018 [ 6 ]).…”
Section: Announcementmentioning
confidence: 77%
“…So far, complete genome sequences have been reported for 13 strains ( https://www.ncbi.nlm.nih.gov/genome/browse#!/prokaryotes/461/ ), of which six were isolated from Mine Hot Spring. Comparative genomic analyses ( 3 ) of these six strains ( 4 7 ) revealed high (≥98.53%) average nucleotide identities (ANIs) to each other, supporting habitat-specific genomic conservation. In this study, to gain insight into the habitat-dependent evolutionary patterns of T. thermophilus , we investigated the genomes of four T. thermophilus strains that were newly isolated from Arima Hot Spring in Japan (34.7974 N, 135.2494 E).…”
Section: Announcementmentioning
confidence: 82%
“…Due to its high-temperature adaptation at around 70°C, Thermus has great biotechnological potential as a source of thermophilic enzymes, as exemplified by Taq DNA polymerase ( 4 ). Since the discovery of T. aquaticus , many Thermus strains have been isolated from thermal areas worldwide ( 5 11 ).…”
Section: Announcementmentioning
confidence: 99%